SIPER: Development of a Web-Based Library Information System at SMK Negeri 7 Makassar Using the Agile Method - Irene Boli; Amirah Putri; Insyira Syahwa Naswari; Muhammad Nur Faiz; Ahmad Khairul Shiddiq (Journal of Digital Technology and Computer Science, 2025)
The development of a web-based library information system at SMK 7 Makassar uses the Agile method to improve service efficiency through digitizing the process of managing books, members, borrowing, and reporting. Agile was chosen because of its flexibility in adjusting the system to user needs through iteration and continuous collaboration. The results of testing 11 main features such as login, add/edit/delete book data, add members, borrow, return, book search, transaction reports, logout, and notifications showed that all functions were running well (100% valid). This system is considered responsive, user-friendly, and ready to be implemented to support the needs of a modern, technology-based library.